Two-Level Game Analysis on US Decision to Withdraw from the Trans-Pacific Partnership (TPP) - Mahendra, Yusril Ihza; Safira, Radina; Muhidin, Sitti Navisah (Insignia: Journal of International Relations, 2023)
This study analyzes the reasons behind the U.S. withdrawal from the Trans-Pacific Partnership (TPP) in 2017. Using descriptive methods and Two-level Game theory as an analytical tool supported by secondary data, we found some domestic factors driving this policy. First, different preferences existed between the government as the “chief negotiator” and interest groups and public opinion representing domestic interests. Two-level game theory explains that international agreement can only be ratified if the win-set negotiations are in overlapping conditions or where international and domestic preferences find a meeting point. However, no common ground between international and domestic preferences resulted in a deadlock. Second, the U.S. public strongly resisted the agreement. Public opinion and hearings are factors that, to some extent, can become obstacles for national governments in international negotiations. Ratification is not only carried out through a formal process (legislative approval) but also through an informal process (public opinion and approval). In addition, the election of Donald Trump, who carried protectionist values with his “America First” slogan, strengthened the position of the opposing groups and those who embraced protectionist values. Therefore, the election of Trump as the president marked the end of the TPP debate because both the executive as the “chief negotiator” and the dominant domestic group rejected the ratification. Keywords: Trans-Pacific Partnership, Two-Level Game Theory, United States